2009
DOI: 10.1186/1476-4598-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of growth, migration and invasion of highly-metastatic human breast cancer cells by berbamine and its molecular mechanisms of action

Abstract: Background: Breast cancer is the second leading cause of cancer related deaths among females worldwide. Berbamine (BER), a kind of bis-benzylisoquinoline alkaloid, has been used to treat clinical patients with inflammation and cancer for many years in China. The purpose of this study is to investigate the activity of BER against highly-metastatic human breast cancer and its molecular mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 45 publications
10
97
0
Order By: Relevance
“…Activation of p-Akt and the NF-jB/Bcl-2 pathway leads to inhibition of chemotherapy-induced apoptosis, which results in treatment resistance (Wang et al 1996). Our previous results confirmed that suppression of Akt and the NF-jB/Bcl-2 pathway by anticancer agents inhibited growth and induced apoptosis and cell cycle arrest in A549 cells and breast cancer MDA-MB-231 cells (Wang et al 2009;Yu et al 2009). In the present study, we indicated that bufalin and the inhibitor of PI3 K/Akt (LY294002) and of NF-jB (Bay) inhibited the A549 cell proliferation and the PI3 K/Akt and NF-jB pathway by suppressing the phosphorylation and expressions of Akt and NF-jB and activating the apoptotic pathway of Bcl-2/Bax-mitochondrial-caspase-3 in A549 cells.…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein supporting
confidence: 75%
See 2 more Smart Citations
“…Activation of p-Akt and the NF-jB/Bcl-2 pathway leads to inhibition of chemotherapy-induced apoptosis, which results in treatment resistance (Wang et al 1996). Our previous results confirmed that suppression of Akt and the NF-jB/Bcl-2 pathway by anticancer agents inhibited growth and induced apoptosis and cell cycle arrest in A549 cells and breast cancer MDA-MB-231 cells (Wang et al 2009;Yu et al 2009). In the present study, we indicated that bufalin and the inhibitor of PI3 K/Akt (LY294002) and of NF-jB (Bay) inhibited the A549 cell proliferation and the PI3 K/Akt and NF-jB pathway by suppressing the phosphorylation and expressions of Akt and NF-jB and activating the apoptotic pathway of Bcl-2/Bax-mitochondrial-caspase-3 in A549 cells.…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Protein supporting
confidence: 75%
“…Flow cytometry for cell cycle analysis and apoptosis These were done according to our published methods (Wang et al 2009;Yu et al 2009;Zhang et al 2000). In brief, A549 cells were treated for 48 h with bufalin at concentrations of 0, 2.5, 5, and 10 lM.…”
Section: Cell Culture and In Vitro Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry for cell cycle analysis and apoptosis These were done according to our published methods (Wang et al 2009;Yu et al 2009;Zhang et al 2000Zhang et al , 2012a. In brief, LLC cells were treated for 48 h with sodium valproate (VPA, 0.5 mM), coumarin-3-carboxylic acid (HCCA, 0.064 mM), or in combination of VPA (0.5 mM) and HCCA (0.064 mM).…”
Section: Cell Culture and In Vitro Proliferation Assaymentioning
confidence: 99%
“…Two of the major biological characteristics of cancer cells are their unusual growth and metastasis, which combined is the major cause of morbidity and mortality in several patients with the disease [112]. Metastasis occurs in approximately half of the cases with apparently localized breast cancer, and death occurs in majority of the cases from the spreading of these cancer cells and their ultimate proliferation at secondary sites [113].…”
Section: Chapter 5 Novel Therapeutic Compound Suppresses Breast Tumomentioning
confidence: 99%